African meditations - Sarr, Felwine, 1972- (Univocal book., 2023)
"African Meditations is a unique contemporary portrait of a young philosopher and creative writer as he seeks to establish himself as a teacher upon his return to Senegal, his homeland, after years of study abroad. It is a seamless blend of autobiography, journal entries, and fiction; aphorisms and brief narrative sketches; humor and Zen reflections"--